Pengaruh Pelatihan Kerja, Lingkungan Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan PT Sinar Pematang Mulia II - Wati, Afrida; Septayuda, Irwan (CV. ITTC INDONESIA, 2024)
This study aims to examine the influence of job training, work environment, and work discipline on employee performance at PT Sinar Pematang Mulia II. The research adopts a population approach using a total sampling technique. Data was collected through questionnaires distributed to 45 respondents. The research method employed is quantitative with a causal associative explanation. The data analysis conducted includes data quality tests, classical assumption tests, multiple linear regression analysis, determination coefficient tests, and hypothesis testing. The results indicate that job training and work environment variables have a positive effect on employee performance. Conversely, work discipline has a negative impact on employee performance at PT Sinar Pematang Mulia II.